2022
DOI: 10.2147/bctt.s348060
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies Against Triple-Negative Breast Cancer: An Updated Review

Abstract: Triple-negative breast cancer (TNBC) is associated with an increased risk of early recurrence and distant metastasis, as well as the development of therapeutic resistance and poor prognosis. TNBC is characterized by a wide range of genetic, immunophenotypic, morphological, and clinical features. TNBC is coined to describe cancers that lack estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). As a result, hormonal or trastuzumab-based treatments are ineffectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 44 publications
(47 reference statements)
0
42
0
Order By: Relevance
“…Targeting the DNA repair and response mechanisms, p53, and cell proliferation mechanisms are some of the therapeutic targets for TNBC management. New therapy targets found in recent molecular characterization of TNBCs include tyrosine and non-tyrosine kinases, PARP1 , AR , immune-checkpoints, and epigenetic proteins [ 162 ]. Great effort is being made to find suitable therapies for TNBC patients via the targeting of a specific molecular features of this tumor type.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the DNA repair and response mechanisms, p53, and cell proliferation mechanisms are some of the therapeutic targets for TNBC management. New therapy targets found in recent molecular characterization of TNBCs include tyrosine and non-tyrosine kinases, PARP1 , AR , immune-checkpoints, and epigenetic proteins [ 162 ]. Great effort is being made to find suitable therapies for TNBC patients via the targeting of a specific molecular features of this tumor type.…”
Section: Discussionmentioning
confidence: 99%
“…For the particular case of TNBC there is still an urgent need to develop efficient therapies. 54,55 Gene therapies have a real potential for the development of targeted anticancer therapeutics. 56,57 Previous results from our group highlight the potential of SNs for the development of new cancer therapeutics.…”
Section: Development Of Cationic Putrescine Nanosystemsmentioning
confidence: 99%
“…51 Therefore, targeting EMT is a strategy to treat triple-negative BC. 52 In addition, these CSC properties are considered to be closely correlated with tumor initiation, progression and metastasis, as well as resistance to chemotherapy. [53][54][55] Our previous studies have shown that OVOL2 inhibits CRC and BC migration and invasion through inhibiting the EMT by inhibiting Wnt and TGF-β signaling.…”
Section: Discussionmentioning
confidence: 99%